PREENCHENDO A LACUNA ENTRE A INTERAÇÃO SOCIAL E A INDIVIDUAL ATRAVÉS DE DIÁLOGO COLABORATIVO NA APRENDIZAGEM DE INGLÊS COMO LÍNGUA ESTRANGEIRA - Vidal, Rejane Teixeira (Intercâmbio, 2010)
Study of negotiated interaction via collaborative dialogue in metatalk tasks. Through “noticing”, “hypothesis formulation and testing” revealed in dialogue with the self and with the other by means of “metatalk” learners construct, co-construct and reconstruct their interlanguage developing it further.